RANCANG BANGUN PISAU MESIN PENCACAH PLASTIK TIPE PET DAN LDPE - Maulana, Sandy Riyaldy; Nuhgraha, Yoddy Agung (Jurnal Mahasiswa Terapan; Vol 2 No 1 (2025): Jurnal Mahasiswa Terapan, 2025)
Household plastic waste is one of the environmental problems that continues to increase due to its non-biodegradable nature. One effective solution is recycling plastic through shredding processes, which reduce its size and make it easier to reprocess. This study focuses on the design and fabrication of plastic shredder blades using spring steel from used leaf springs as an alternative material that is inexpensive, durable, and easily available. The research stages include blade design, material selection, and manufacturing processes consisting of cutting, bevel profile forming, heat treatment (hardening and tempering), welding to the rotor, finishing, and sharpening. Performance testing was carried out to evaluate shredding capacity and the quality of shredded plastic, specifically PET, HDPE, and LDPE. The results show that the spring steel blades were successfully produced with a shredding capacity of 14.29–21.43 kg/hour. The quality of shredded output varies according to plastic type, with LDPE producing finer and more uniform particles. Economically, the blade can be manufactured at approximately Rp625,000 per unit and demonstrates sufficient wear resistance after heat treatment, although it becomes dull faster compared to SKD-11 material. Therefore, spring steel blades can be considered an effective and economical alternative for small- to medium-scale plastic shredding machines.